ICT elements of virtual learning supporting instructional materials for caregivers of student with autism - Ab Mahadi, Mudrikah (2025)
Students with Autism Spectrum Disorder (ASD) experience considerable challenges in adapting to virtual learning environments due to their need for structured, consistent, and sensory-sensitive instruction. The COVID-19 pandemic accelerated the transition to online learning, exposing significant gaps in caregiver support, instructional design, and the use of ICT tools suitable for autistic learners. This study aims to address these challenges by developing instructional design elements that integrate relevant ICT components to support caregivers in facilitating virtual learning. The research objectives are to identify the issues and challenges associated with ICT elements during virtual learning for autistic students, to design instructional design elements that assist caregivers in using ICT tools effectively, and to evaluate the extent to which these elements are tailored to meet the specific needs of autistic learners.